KOMPOSISI MUSIK GAMAT SEBAGAI BENTUK PENGEMBANGAN KESENIAN MELAYU MINANGKABAU - Rizaldi Rizaldi; Yon Hendri; Bambang Wijaksana (Pascasarjana Institut Seni Indonesia Padang Panjang, 2018)
ABSTRACT Gamat is one of the types of Minangkabau traditional music that flourishes in the west coast area, Sumatera Barat. This music is born as the result of assimilation among Minangkabau indigenous culture and western culture (acculturation), that until today still lives in Minangkabau society, especially Padang city. Even though gamat music is born from the acculturation of indigenous culture and western culture but for the people of Padang city, that music is already considered as the possession and part of their tradition so there is the responsibility of those people to conserve it. The ensemble form of gamat music consists of the combination of vocal and instrumental, that traditionally uses violin, accordion, guitar, gendang, and bass as its instruments. Vocal has a role as song carrier that its lyric is in the form of metaphorical Minangkabau pantuns. However, in the research of this artwork, gamat is turned into the composition by using the approach of the conventional musical technique presented in the form of the orchestra. Keywords: gamat music, the composition of gamat music, the performance of gamat music ABSTRAK Gamat adalah salah satu jenis musik tradisional Minangkabau yang berkembang di daerah pantai barat, Sumatera Barat. Musik ini lahir akibat perbauran antara budaya pribumi Minangkabau dan budaya Barat (akulturasi), yang sampai sekarang tetap hidup dalam masyarakat Minangkabau, khususnya di Kota Padang. Walaupun musik gamat lahir dari akulturasi budaya pribumi dan budaya Barat, tetapi bagi masyarakat Kota Padang musik tersebut sudah dianggap sebagai milik dan bahagian dari tradisi mereka, sehingga ada rasa tanggung jawab bagi masyarakat tersebut untuk melestarikannya. Bentuk ensambel musik gamat terdiri atas gabungan vokal dan instrumental, yang secara tradisional menggunakan biola, akordeon, gitar, gendang, dan bas sebagai instrumennya. Vokal berperan sebagai pembawa lagu yang liriknya berupa pantun-pantun Minangkabau yang bersifat metafor (kiasan). Akan tetapi, dalam penelitian karya seni ini, gamat diubah menjadi komposisi dengan menggunakan pendekatan teknik musik konvensional yang disajikan dalam bentuk Orkestra.